Analysis of a 7‐year national online audit of the management of open reconstructive urethral surgery in men. (27th September 2019) - Payne, Stephen R.; Fowler, Sarah; Mundy, Anthony R.
Abstract : Objective: To conduct an audit of the management of urethral pathology in men presenting for reconstructive urethral surgery in the UK. Methods: Between 1 June 2010 and 31 May 2017, data on men presenting with urethral pathologies requiring reconstruction were entered onto a secure online data platform. Surgeon‐entered information was collected in 95 fields regarding the stricture aetiology, prior management, mode of presentation, type of surgery and outcomes, with a potential 283 variable responses in the 95 fields. Data were analysed to compare UK practice with that reported in the contemporary literature and with guidelines. Results: Data on 4809 men were entered by 39 centres and 50 surgeons. Field completeness was 70.7%, 74.3% and 53.7% for preoperative, operative and follow‐up data, respectively. Referral for stricture reconstruction frequently followed two prior endoscopic procedures and the stricture was not always assessed anatomically before surgery. Urinary retention was a common symptom in men awaiting reconstruction. Short unifocal strictures of the anterior urethra were the commonest reason for referral, whilst lichen sclerosus and hypospadias generated a significant volume of revisional stricture surgery. Lower numbers of very complex interventions are required for the management of posterior urethral pathology. Although precise criteria for determining success are not clear, management of urethral reconstruction in the UK was found to have a low risk of Clavien–Dindo grade 3 or higher complications, and was associated with outcomes similar to those reported in contemporary series except in the management of posterior urethral fistulae. Conclusions: Online databases can provide volume data on the management of reconstructive urethral surgery across a multiplicity of centres in one country. They can also indicate compliance with accepted standards of, and expected outcomes from, this tertiary practice.